Rock strength obtained from core samples and borehole wall - the effect of drilling induced damageinstabilities - Valley, Benoît; Bahrani, N.; Kaiser, P.K. (My University, 2010)
Borehole breakouts are accepted as one of the best indicators of in-situ principal stress orientation. However, the estimation of the stress magnitude from breakouts is still controversial. One prerequisite to derive stress magnitude from borehole wall failure is to have an independent estimate of the strength of the borehole wall. Zoback et al. (2003) suggest assuming that the Uniaxial Compressive Strength (UCS) from core samples is an acceptable estimate of borehole wall strength, but it has been shown that when drilling in relatively high stress environments core may be damaged, resulting in significantly reduced core strengths (e.g. Martin and Stimpson, 1994). Such core damaging processes are highly probable in stress environments relevant for breakout formation. Thus, an underestimation of UCS due to core damage could lead to an underestimation of in-situ stress magnitude from breakout back-analyses. Preliminary results from the numerical analyses presented here suggest that damage in the core initiates long before any damage occurs in the borehole wall. It is thus suggested that in relatively high-stress situations, strength evaluation from borehole geophysics or from breakouts back-analyses (in situations where the complete stress tensor is independently estimated) delivers a better estimate of the in-situ intact rock strength than laboratory tests. Work is underway to propose solution for the unbiased estimation of in-situ intact rock strength from borehole observations.
, 2010